An analysis of the stakeholder model of public boards and the case of school governing bodies in England and Wales. (January 2017) - Connolly, Michael; Farrell, Catherine; James, Christopher
This article analyses the stakeholder model of boards that is widely used in public and third sector institutions in England and Wales. The central tenet of this model is that such institutions should be strategically led by individuals who are representative of and from the groups that have an interest in them. The article focuses in particular on the operation of the stakeholder model of governing bodies of schools in England and Wales where a range of stakeholders including teachers, parents and the community are represented. The issues that arise from this stakeholder model of governing are analysed and the alternatives to it are considered. A significant alternative is the skills-based model, where boards are constituted on the basis of their expertise and not their interest in the institution. This skills-based model is becoming more prominent in the way governing bodies of academy schools in England are constituted and this is certainly the direction of travel outlined in the 2015 regulations. The article reviews the stakeholder model for the governance of schools at a time when there is much interest in the skills-based approach. The wider implications of shifting from a stakeholder to a skills-based model of public board membership are considered.